1999
DOI: 10.1126/science.286.5449.2504
|View full text |Cite
|
Sign up to set email alerts
|

Inattentional Blindness Versus Inattentional Amnesia for Fixated But Ignored Words

Abstract: People often are unable to report the content of ignored information, but it is unknown whether this reflects a complete failure to perceive it (inattentional blindness) or merely that it is rapidly forgotten (inattentional amnesia). Here functional imaging is used to address this issue by measuring brain activity for unattended words. When attention is fully engaged with other material, the brain no longer differentiates between meaningful words and random letters, even when they are looked at directly. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
153
6

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(175 citation statements)
references
References 32 publications
16
153
6
Order By: Relevance
“…At a peak time of day, young adults showed no implicit memory for the distracting words, even though the words were in the centre of objects they were examining. This finding is consistent with earlier reports of IB in young adults (e.g., Rees et al, 1999) and with the problem solving findings of May (1999).…”
Section: Scoringsupporting
confidence: 93%
See 1 more Smart Citation
“…At a peak time of day, young adults showed no implicit memory for the distracting words, even though the words were in the centre of objects they were examining. This finding is consistent with earlier reports of IB in young adults (e.g., Rees et al, 1999) and with the problem solving findings of May (1999).…”
Section: Scoringsupporting
confidence: 93%
“…Using a modification of Rees et al (1999), participants made same/different judgements on line-drawings superimposed with task-irrelevant letter strings. Memory for the distractors was subsequently tested using an implicit memory task.…”
Section: Introductionmentioning
confidence: 99%
“…2 A). In a related study, Rees et al (1999) showed that activations associated with words were not elicited when subjects performed a concurrent, highly demanding object workingmemory task. Thus, like the processing of visual motion, even word processing seems to require attention, contrary to claims for full automaticity (Van Orden et al, 1988;Menard et al, 1996).…”
Section: Interactions Between Control and Target Areasmentioning
confidence: 96%
“…Second, the VWFA responds more to words or to pseudo-words than to random consonant strings that violate orthographic constraints (Beauregard et al, 1997;Büchel et al, 1998;Cohen et al, 2002;Price et al, 1996;Rees et al, 1999;Xu et al, 2001). 3 This suggests that it has become sensitive to orthographic rules in the subject's language, which are matters of cultural convention.…”
Section: Functional Specializationmentioning
confidence: 99%